Studi Profitabilitas: Antaseden dan Dampaknya Terhadap Nilai Perusahaan - Muhammad Firza Alpi; Soulthan Saladin Batubara (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
The purpose of this research is to find out and analyze the effect of capital structure, corporate growth, and profitability partially and simultaneously on the value of the company on coal mining companies listed on the Indonesia Stock Exchange. The population of this study is a coal mining company listed on the Indonesia Stock Exchange as many as 21 companies with observation years 2013 to 2017. The sample is selected using the purposive sampling method. The data is processed using the data panel's regression statistics test method. The results of this study prove that the capital structure and profitability have a partial effect on the value of the company in coal mining companies listed on the Indonesia Stock Exchange. While the company's growth has no effect on the value of the company in coal mining companies listed on the Indonesia Stock Exchange. Simultaneously, the company's capital structure, growth and profitability have a simultaneous effect on the value of the company in coal mining companies listed on the Indonesia Stock Exchange.